Systemically Achievable Doses of Beer Flavonoids Induce Estrogenicity in Human Endometrial Cells and Cause Synergistic Effects With Selected Pesticides - Aichinger, Georg; Bliem, Gloria; Marko, Doris (Frontiers in Nutrition, 2021)
Some prenylated polyphenols originating from hops, which are thus natural constituents of beer, have been discussed critically for their agonistic potential towards estrogen receptors. So far, little attention has been attributed to the fact that humans are typically not exposed to isolated compounds, but to mixtures which for example might comprise in addition to hop flavonoids further xenoestrogens, e.g. certain pesticides used for plant protection of hops and barley. Thus, we used the alkaline phosphatase assay to assess combinatory estrogenic effects of three signature compounds – xanthohumol, 8-prenylnaringenin and iso-xanthohumol - on Ishikawa cells in a combination that resembled the concentration ratios observable in beer. Moreover, we added this natural flavonoid pattern to a mixture of representative estrogenic pesticides to assess their combined effects. Using state-of-the-art statistical tools, we observed cumulative to slightly synergistic effects between isolated flavonoids as well as the flavonoid and the pesticide mixture. Of potential importance, these effects were found at low nanomolar hop polyphenol concentrations that one can reasonably expect to occur in vivo after the consumption of strongly hopped beer. Taken together, our results imply that cumulative/synergistic estrogenicity should be explored in detail and urgently be incorporated into risk assessment of prenylated chalcones.